2013
DOI: 10.1080/00207144.2013.784066
|View full text |Cite
|
Sign up to set email alerts
|

Are Highly Hypnotizable People Naturally Aware Of Their Hypnotic Talents?Implications for Human Potentialities

Abstract: This article investigated the degree to which high hypnotizables are aware of their capability and assessed their ability to produce it without guidance from a hypnotist. Qualitative data suggest that most participants reported being surprised by their hypnotic responsiveness and the realness of the suggestions. Quantitative data tended to support this trend, in which participants had higher overall responsiveness scores, both objectively and subjectively, when the suggestions were given by a hypnotist compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In this case, active hypnosis is easily associated with creative emotions, so that the psychological reactions bring the readiness for creativity (Raikov, 1992). For instance, when the goal is to activate the thinking, participants of the hypnosis reported that it was easier to experience the suggested effects when given by the hypnotist (Mohl, 2013).…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…In this case, active hypnosis is easily associated with creative emotions, so that the psychological reactions bring the readiness for creativity (Raikov, 1992). For instance, when the goal is to activate the thinking, participants of the hypnosis reported that it was easier to experience the suggested effects when given by the hypnotist (Mohl, 2013).…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Time spent sleeping was predicted to attenuate REST effects as it shortens the time Pts are actively engaged in attempting to adapt to reduced levels of stimulation. Barabasz (1982) demonstrated enhanced hypnotizability (Mohl, 2013) and lower pain scores following 6 hours of chamber REST when a lighted condition using Ganzfeld goggles was employed (Ganzfeld goggles allow near-full light transmission but prevent focus on images). In contrast, Barabasz, Barabasz, Dyer, and Rather (1993) employed 3, 6, 12, and 24 hours of unlighted chamber REST in the treatment of alcohol overconsumption.…”
mentioning
confidence: 98%